Seasonal patterns and environmental drivers of protistan plankton along a terrestrial–marine gradient in Isfjorden (Svalbard) - Dąbrowska, Anna Maria; McGovern, Maeve; Mazurkiewicz, Mikołaj; Poste, Amanda (Frontiers in Marine Science, 2025)
The Arctic is undergoing rapid environmental transformation, with intensified glacial and permafrost melt fundamentally altering freshwater discharge regimes and biogeochemical fluxes to coastal fjord systems. Here, we investigate how seasonal meltwater dynamics shape protistan plankton communities along a terrestrial – marine gradient in Isfjorden (Svalbard) during the exceptionally warm year of 2018. Sampling across three distinct melt season stages – pre-freshet (May), spring freshet (June), and late summer runoff (August) – revealed pronounced temporal and spatial shifts in community structure, strongly linked to evolving environmental gradients. In May, cold, clear, unstratified waters and marine nutrient inputs supported a typical late spring bloom, led by Phaeocystis pouchetii, which significantly contributed to the particulate organic carbon pool, and was followed by diatoms of the genera Chaetoceros and Thalassiosira. The June freshet triggered sharp stratification and nutrient enrichment from glacial and terrestrial sources, driving an unprecedented proliferation of small flagellates, notably Chrysochromulina and two morphologically distinct, yet unidentified taxa. However, by August, escalating turbidity from intensified meltwater inputs and sediment resuspension severely constrained photic conditions, suppressing protistan biomass despite sustained nutrient availability. Across the season, community dynamics were governed by complex interactions between nutrient supply, light limitation, and physical forcings such as stratification and advection. Our findings suggest that ongoing Arctic warming may increasingly favor opportunistic, small flagellates over traditional diatom-dominated blooms, with major implications for carbon cycling and food web dynamics in Arctic fjords.